An Analysis of English Teachers’ Problems in Implementing the Independent Curriculum at Junior High School - Mirnayanti; Zulfah Fakhruddin; Ambo Dalle; Abdul Haris Sunubi; Magdahalena Tjalla (Universitas Muhammadiyah Palu, 2024)
This research aims to identify inhibiting factors in the implementation of the Merdeka Belajar curriculum. The study was conducted at Upt Smp 1 Mattiro Bulu, Upt Smp 2 Mattiro Bulu, Upt Smp 3 Mattiro Bulu, Upt Smp 1 Suppa, and Upt Smp 4 Suppa. The research problem revolves around the issues faced by English teachers in implementing the Merdeka curriculum. Data were collected through questionnaires, employing a quantitative approach. The research focused on: 1) Internal Factors: Student Motivation, Student Attitude, and Student Interest. 2) External Factors: Parental Support, School Leadership, School Facilities, Learning Systems, Learning Materials, Teacher Competence, and Time. The results indicate that the identified inhibiting factors include Internal Factors such as Student Motivation, Student Attitude, and Student Interest. However, the highest contributing factor is Student Motivation. External inhibiting factors include Parental Support, School Leadership, School Facilities, Learning Systems, Learning Materials, Teacher Competence, and Time. The most significant factor here is Learning Materials. According to the findings, teachers do not face issues related to Parental Support and School Leadership. This research also indicates that inhibiting factors in implementing the Merdeka Belajar curriculum vary across schools based on their specific conditions. The identification of inhibiting factors provides recommendations to the Ministry of Education and Culture as the regulator and policymakers in Junior High Schools.